Functional Gastrointestinal Disease in Autism Spectrum Disorder: A Retrospective Descriptive Study in a Clinical Sample - Penzol, María José; Salazar de Pablo, Gonzalo; Llorente, Cloe; Moreno, Carmen; Hernández, Patricia; Dorado, Maria Luisa; Parellada, Mara (Frontiers in Psychiatry, 2019)
Introduction: Autism spectrum disorder (ASD) is a heterogeneous group of neurodevelopmental disorders with complex multifactorial etiologies. Medical comorbidities are common in ASD and include functional gastrointestinal disorders (fGID), which are reported in 30-70% of patients. In this research study, we aimed to systematically assess the prevalence of gastrointestinal problems in ASD and describe their clinical correlates. Methods: In this retrospective study, we reviewed the medical records of all patients admitted to the Comprehensive Medical Program for ASD (AMITEA) at Gregorio Marañón University General Hospital from January 2012 to December 2015. All patients fulfilled the clinical criteria for ASD (DSM-IV-TR). In addition to fGID, epidemiological and clinical variables were collected at intake. Clinical and demographic features were compared among subjects with and without comorbid gastrointestinal problems. Results: The analyses included all patients with documented information about presence/absence of fGID (n=845; 95% of patients). Ages ranged from 1 to 53 years (mean=10.52; SD=8.92; 80.4% males). At least one fGID was present in 30.5% of patients, constipation being the most prevalent (47.4% of fGID patients); fGID were significantly associated with intellectual disability (ID) (p=0.017), sleep disorders (p=0.012), and prescription of psychopharmacological treatment (p=0.019). Conclusions : Almost one-third of ASD patients in our sample had at least one fGID. The presence of fGID was associated with ID, sleep problems and with behavioral problems (as measured by the prescription of psychotropic drugs). This subsample of ASD patients with fGID deserves particular attention in future research projects, focusing on specific phenotypic characteristics and overlapping biological markers that may underlie both pathologies.